(untitled) (Archives of Pediatrics of Uruguay, 2021)
Coagulase negative staphylococcus (CoNS) are commonly isolated microorganisms whose clinical importance may be difficult to establish due to their role as part of our usual skin microbiota. These pathogens have gained relevance in neonatal population due to an improvement in neonatal care that determine longer survival rates and hospitals stays. Neonatal endocarditis is also affected by these microorganisms and particularly by the use of central intra vascular lines for long periods of time. In this clinical case we introduce a severe preterm patient who developed a CoNS endocarditis and discuss the characteristics of CoNS infections and endocarditis in preterm newborns as well as some antibiotic vigilance principles.